Optical and structural properties of ZnO, TiO2 and V2O5 modified lithium borate glasses/glass-ceramics - Arya, Sunil Kumar (My University, 2016)
This thesis describes the structural, thermal, optical and dielectric properties of lithium borate glasses and glass-ceramics modified by ZnO, TiO2 and V2O5. The samples are synthesized by melt-quench technique at 1200 °C in re-crystallize Al2O3 crucible. The as prepared samples are characterized using various analytical techniques. The obtained results are correlated with theoretical composition dependent parameters. The present work has been divided into five chapters followed by relevant references.  Chapter 1 describes the evolution and introduction of glasses and glass-ceramics. The role of different glass components like former, modifier and intermediate oxides and their influences on different properties have also been discussed. Furthermore, different requirements for glass formation have been described. Applications of glasses in modern life have also been summarized and the chapter ends with the motivation behind the study.  Chapter 2 reviews the literature and give an idea that lithium borate glasses and glass-ceramics are the focus of scientific interest due to their random structures and applications. The presence of transition metal oxides in glass composition modifies the properties of glasses due to variable transition states which formed locally different structural units in glass matrix. For instance, the character of chemical bonds and structural rearrangement occurs in the glass network due to incorporation of vanadyl ion (VO2+), which changes the optical, thermal and dielectric properties of the glasses. On the other hand, small amount of titanium oxide acts as a nucleating agent and it helps in reducing the optical band gap of material. Researchers have also found titanium oxide doped borosilicate glasses are suitable for microelectronic applications. Additionally, these borate glasses are often used as dielectric and insulating shielding materials. Moreover, the wide optical band gap of these glasses can be exploited to use in non-linear optics.  Chapter 3 describes the synthesis of glasses and glass-ceramics using stoichiometric ratio of various high purity (99.9%) constituents. The constituents were mechanically mixed using agate mortar and pestle in wet media (acetone) for 2 h. The powder was melted and air quenched using copper plates and further annealed to remove the stresses. The synthesis process and characterization of the as prepared glasses and glass-ceramics have been discussed in details in this chapter. The two series 30Li2O–55B2O3–5ZnO–xTiO2–(10-x)V2O5, (0≤x≤10) and 30Li2O–55B2O3–(15-x)ZnO–xV2O5, (0≤x≤7.5%) of glasses were synthesized named as TV-series and ZV-series, respectively. In these series, the content of V2O5 replaced by TiO2 and ZnO respectively. The important techniques used in characterization are X-rays diffraction (XRD), FTIR spectroscopy, Raman spectroscopy, Electron Paramagnetic Resonance (EPR), Scanning Electron Microscope (SEM), Microwave Plasma Atomic Emission Spectroscopy (MP-AES), Transmission Electron Microscopy (TEM), Differential Thermal Analysis (DTA) and Thermogravimetric Analysis (TGA), UV-Visible spectroscopy, Photoluminescence spectroscopy and impedance spectroscopy.  Chapter 4 deals with the interpretation of the data obtained from various characterization techniques. It has been found that the higher content of titanium prevent to the formation of glass and form in-situ nanocrystalline phase of TiO2, which increases the dominancy of electronic conduction along with decreased activation energy i.e. 0.21 eV in TV-series glasses. The density of the glass also increases with the increasing titanium content in the glass compositions. The lowest dielectric constant is observed for TV-0.0 nanocrystalline glass ~3 at room temperature and 1 MHz, with excellent stability with respect to temperature and frequency. The highest dielectric constant is observed for TV-7.5 glass ~20 at 100 Hz at room temperature. The present glasses could be excellent materials for low-k applications such as microelectronics. Optical studies indicate that Urbach energy decreases and direct/indirect band gap energy increases, respectively, with the increase in titanium oxide content. The direct and indirect band gaps decreases with the decreasing vanadium content indicating that the presence of vanadium ions introduces more random open structure in the glass network as compared to the zinc ions in ZV-series glass. EPR results indicate that hyperfine structure arising from the transitions between an unpaired electron (s = 1/2) with VO2+ (V4+ ions) nucleus with nuclear spin 7/2. These spectra were analyzed by assuming C4V symmetry of V4+ ions. The highest crystallization energy was obtained for glass containing maximum content of TiO2.  Chapter 5 exhibits the conclusion drawn from structural, thermal and optical properties of the prepared glasses and glass-ceramics. The chapter also includes the future scope for study, which includes an idea about phase dependent properties in glass-ceramic.
Keywords: Glasses, Optical properties, EPR, Dielectric, Conducivity